ANALISIS TERHADAP PENGATURAN KEBEBASAN HUKUM BERPENDAPAT MELALUI MEDIA INTERNET - Etika Dwi Hardiyaningsi; Meri Yarni (Limbago: Journal of Constitutional Law, 2022)
This study aims to: 1) To find out how the legal protection of the regulation of freedom of expression through the internet media, 2) To find out how the form of the Indonesian state's obligation to protect the right to freedom of expression on the internet media. The method used in this stkebebudy is the normative juridical method, which is a legal research that is prescriptive not descriptive as in social and natural sciences, the approach is based on the main legal material by examining theories, concepts, legal principles and regulations. legislation. The results obtained are: 1). Freedom of expression in Indonesia, both orally and in writing, has been guaranteed and has been regulated in the rules contained in the 1945 Constitution until it is contained in Law Number 39 of 1999 concerning Human Rights, Law Number 9 of 1998 concerning Freedom to Express Opinions in Public, Law Number 12 of 2005 concerning Ratification of the International Covenant On Civil And Political Rights (International Covenant on Civil and Political Rights), 2) The rights and obligations of the state (government) and citizens are regulated in law - The 1945 Constitution is in the fourth paragraph. and Article 281 paragraphs (4) and (5). The fourth paragraph contains the goals and obligations of the state that must be carried out by every government, namely protecting the entire Indonesian nation and the entire homeland of Indonesia, advancing public welfare, educating the nation's life, and implementing world order based on independence, eternal peace, and social justice. Keywords; Freedom of Opinion, Internet.